Seebeck coefficient of silicon nanowire forests doped by thermal diffusion - Elyamny, Shaimaa; Dimaggio, Elisabetta; Pennelli, Giovanni (Beilstein Journal of Nanotechnology, 2020)
Thermoelectric generators made by large arrays of nanowires perpendicular to a silicon substrate, that is, so-called silicon nanowire forests are fabricated on large areas by an inexpensive metal-assisted etching technique. After fabrication, a thermal diffusion process is used for doping the nanowire forest with phosphorous. A suitable experimental technique has been developed for the measurement of the Seebeck coefficient under static conditions, and results are reported for different doping parameters. These results are in good agreement with numerical simulations of the doping process applied to silicon nanowires. These devices, based on doped nanowire forests, offer a possible route for the exploitation of the high power factor of silicon, which, combined with the very low thermal conductivity of nanostructures, will yield a high efficiency of the conversion of thermal to electrical energy.
Keywords: nanowires; Seebeck coefficient; thermal conductivity; thermoelectricity

(untitled) - Bux, S. K.; Blair, R. G.; Gogna, P. K.; Lee, H.; Chen, G.; Dresselhaus, M. S.; Kaner, R. B.; Fleurial, J.-P. (Adv. Funct. Mater., 2009)

(untitled) - Bennett, N. S. (Phys. Status Solidi A, 2017)

(untitled) - Dimaggio, E.; Pennelli, G. (Nanotechnology, 2018)

(untitled) - Gadea Díez, G.; Sojo Gordillo, J. M.; Pacios Pujadó, M.; Salleras, M.; Fonseca, L.; Morata, A.; Tarancón Rubio, A. (Nano Energy, 2020)

(untitled) - Melosh, N. A.; Boukay, A.; Diana, F.; Gerardot, B.; Badolato, A.; Petroff, P. M.; Heath, J. R. (Science, 2003)

(untitled) - Hochbaum, A. I.; Chen, R.; Delgado, R. D.; Liang, W.; Garnett, E. C.; Najarian, M.; Majumdar, A.; Yang, P. (Nature, 2008)

(untitled) - Feser, J. P.; Sadhu, J. S.; Azeredo, B. P.; Hsu, K. H.; Ma, J.; Kim, J.; Seong, M.; Fang, N. X.; Li, X.; Ferreira, P. M.; Sinha, S.; Cahill, D. G. (J. Appl. Phys., 2012)

(untitled) - Pennelli, G.; Nannini, A.; Macucci, M. (J. Appl. Phys., 2014)

(untitled) - Lim, J.; Hippalgaonkar, K.; Andrews, S. C.; Majumdar, A.; Yang, P. (Nano Lett., 2012)

(untitled) - Pennelli, G.; Dimaggio, E.; Macucci, M. (IEEE Trans. Nanotechnol., 2018)

(untitled) - Huang, Z.; Geyer, N.; Werner, P.; de Boor, J.; Gösele, U. (Adv. Mater. (Weinheim, Ger.), 2011)

(untitled) - Kim, J.; Han, H.; Kim, Y. H.; Choi, S.-H.; Kim, J.-C.; Lee, W. (ACS Nano, 2011)

(untitled) - Peng, K.; Yan, Y.; Gao, S.; Zhu, J. (Adv. Funct. Mater., 2003)

(untitled) - To, W.-K.; Tsang, C.-H.; Li, H.-H.; Huang, Z. (Nano Lett., 2011)

(untitled) - Curtin, B. M.; Fang, E. W.; Bowers, J. E. (J. Electron. Mater., 2012)

(untitled) - Xu, B.; Fobelets, K. (J. Appl. Phys., 2014)

(untitled) - Elyamny, S.; Dimaggio, E.; Magagna, S.; Narducci, D.; Pennelli, G. (Nano Lett., 2020)

(untitled) - Dimaggio, E.; Pennelli, G. (Nano Lett., 2016)

(untitled) - Qi, Y.; Wang, Z.; Zhang, M.; Yang, F.; Wang, X. (J. Phys. Chem. C, 2013)

(untitled) - Dimaggio, E.; Narducci, D.; Pennelli, G. (J. Mater. Eng. Perform., 2018)

(untitled) - Krali, E.; Durrani, Z. A. K. (Appl. Phys. Lett., 2013)

(untitled) - Magagna, S.; Narducci, D.; Alfonso, C.; Dimaggio, E.; Pennelli, G.; Charaï, A. (Nanotechnology, 2020)

(untitled) - Pennelli, G.; Elyamny, S.; Dimaggio, E. (Nanotechnology, 2018)

Diffusion in Silicon - Fisher, D. (Scitec Publications, 1998)

(untitled) - Geballe, T. H.; Hull, G. W. (Phys. Rev., 1955)

(untitled) - Brinson, M. E.; Dunstant, W. (J. Phys. C: Solid State Phys., 1970)

(untitled) - Stranz, A.; Kähler, J.; Merzsch, S.; Waag, A.; Peiner, E. (Microsyst. Technol., 2012)

(untitled) - Arora, N. D.; Hauser, J. R.; Roulston, D. J. (IEEE Trans. Electron Devices, 1982)